Assimilates allocation in fruits and leaves of coffee plants cultivated in two altitudes - Laviola, Bruno Galvêas; Martinez, Herminia Emilia Prieto; Salomão, Luiz Carlos Chamhum; Cruz, Cosme Damião; Mendonça, Sebastião Marcos; Paula Neto, Ana (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the allocation of carbohydrates in fruits of Arabic coffee plant during the period comprised among the anthesis and maturation in two different altitudes, as well as, the variation in its content in leaves of these productive branches. The experiment was constituted of the coffee plant variety (Coffea arabica L.) Catuaí IAC-44 cultivated at 720 and 950 m above the sea level in Martins Soares, Minas Gerais State, Brazil. The experimental design was completely randomized with three repetitions using split-plot in time scheme. The altitude of 720 m contributed to an acceleration in the accumulation of starch, total soluble sugar, reducing sugar and non-reducing sugar in coffee plant fruits. The accumulation of starch in the altitude of 720 m preceded the accumulation in the altitude of 950 m, presenting larger earning percentage in the fruit fast expansion stadium. In this stadium, carbohydrate concentrations in leaves in the 3rd and 4th leave pairs of productive branches decreased abruptly indicating that this is the most critic period for the carbohydrate concentrations in leaves. Altitude influenced the extension of the cycle, as well as the assimilate accumulation by fruits and that variation in coffee plant leaves.